Empowering Global Islamic Education Through Arabic Public Speaking - Bashiroh, Ein; Ammar, Farikh Marzuki (Indonesian Journal of Islamic Studies, 2024)
This study examines the role of public speaking in enhancing Arabic language proficiency among teenagers in Islamic education. With Arabic being pivotal in conveying Islamic teachings and public speaking central to da'wah efforts, this research fills the gap in understanding how public speaking can aid language acquisition and foster leadership skills. Surveys and interviews with teenagers attending Islamic educational programs reveal a positive correlation between engagement in public speaking activities and perceived Arabic language proficiency. Participants express increased confidence in communicating Islamic teachings through fluent Arabic language following public speaking training. These findings suggest integrating public speaking into Islamic educational curricula as a means to bridge the gap between traditional education and the contemporary millennial generation, fostering a generation skilled in both Arabic language and confident public speaking for effective da'wah. Highlight: 1. Improved Arabic Skills: Public speaking enhances Arabic language proficiency for teenagers.2. Confidence Boost: Teenagers gain confidence in communicating Islamic teachings through public speaking.3. Education Integration: Public speaking bridges traditional Islamic teachings with millennial generation learning. Keywords: Public Speaking, Arabic Language Proficiency, Islamic Education, Teenagers, Da'wah Efforts